2012
DOI: 10.1186/1471-2164-13-368
|View full text |Cite
|
Sign up to set email alerts
|

The receptor like kinase at Rhg1-a/Rfs2 caused pleiotropic resistance to sudden death syndrome and soybean cyst nematode as a transgene by altering signaling responses

Abstract: BackgroundSoybean (Glycine max (L. Merr.)) resistance to any population of Heterodera glycines (I.), or Fusarium virguliforme (Akoi, O’Donnell, Homma & Lattanzi) required a functional allele at Rhg1/Rfs2. H. glycines, the soybean cyst nematode (SCN) was an ancient, endemic, pest of soybean whereas F. virguliforme causal agent of sudden death syndrome (SDS), was a recent, regional, pest. This study examined the role of a receptor like kinase (RLK) GmRLK18-1 (gene model Glyma_18_02680 at 1,071 kbp on chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 61 publications
(155 reference statements)
1
34
0
3
Order By: Relevance
“…The RLK was shown to have an effect on reducing SCN infections with three different HgType 0s by about 30% in stable transgenics tested in three laboratories and two countries Lightfoot, 2011). Therefore, the RLK GmRLK18-1 (gene model Glyma_18_02680 at 1071 kbp on chromosome 18 of the genome sequence) was thought to be only one of several genes at the rhg1 locus active against nematodes (Cook et al, 2012;Srour et al, 2011). Therefore, the RLK GmRLK18-1 (gene model Glyma_18_02680 at 1071 kbp on chromosome 18 of the genome sequence) was thought to be only one of several genes at the rhg1 locus active against nematodes (Cook et al, 2012;Srour et al, 2011).…”
Section: Rfs1 Rfs2 and Rfs3 Loci Underlying Root Rot Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The RLK was shown to have an effect on reducing SCN infections with three different HgType 0s by about 30% in stable transgenics tested in three laboratories and two countries Lightfoot, 2011). Therefore, the RLK GmRLK18-1 (gene model Glyma_18_02680 at 1071 kbp on chromosome 18 of the genome sequence) was thought to be only one of several genes at the rhg1 locus active against nematodes (Cook et al, 2012;Srour et al, 2011). Therefore, the RLK GmRLK18-1 (gene model Glyma_18_02680 at 1071 kbp on chromosome 18 of the genome sequence) was thought to be only one of several genes at the rhg1 locus active against nematodes (Cook et al, 2012;Srour et al, 2011).…”
Section: Rfs1 Rfs2 and Rfs3 Loci Underlying Root Rot Resistancementioning
confidence: 99%
“…Three groups of scientists have independently isolated and characterized strong candidates for genes functional at the two loci (Rhg1 and Rhg4 on genetic LG-G and A2, respectively) that putatively encode resistance to SCN Cook et al, 2012;Srour et al, 2011). Three groups of scientists have independently isolated and characterized strong candidates for genes functional at the two loci (Rhg1 and Rhg4 on genetic LG-G and A2, respectively) that putatively encode resistance to SCN Cook et al, 2012;Srour et al, 2011).…”
Section: New Understandings Of the Relationship Between Sudden Death mentioning
confidence: 99%
“…Ruben et al (2006) fine mapped the rhg1 locus and identified a single receptor like kinase ( RLK; leucine rich repeat transmembrane-protein kinase ) as candidate resistance gene. Srour et al (2012) characterized the GmRLK18-1 , the gene underlying Rhg1 locus, in transgenic and heterozygous plants and demonstrated that the dominant allele confers reported pleiotropic resistance to SCN and sudden death syndrome (SDS) caused by Fusarium virguliforme . In the absence of Rhg4 , the GmRLK18-1 had provided partial resistance to SCN and conferred nearly complete resistance to SDS, whereas, in the presence of Rhg4 , the plants with the GmRLK18-1 transgene were fully resistant to SCN as well as SDS (Srour et al, 2012).…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 99%
“…Srour et al (2012) characterized the GmRLK18-1 , the gene underlying Rhg1 locus, in transgenic and heterozygous plants and demonstrated that the dominant allele confers reported pleiotropic resistance to SCN and sudden death syndrome (SDS) caused by Fusarium virguliforme . In the absence of Rhg4 , the GmRLK18-1 had provided partial resistance to SCN and conferred nearly complete resistance to SDS, whereas, in the presence of Rhg4 , the plants with the GmRLK18-1 transgene were fully resistant to SCN as well as SDS (Srour et al, 2012). In vitro , the purified LRR domain of GmRLK18-1 has been shown to bind with the CLE peptides of plant origin known to involve in tracheary element inhibition (Afzal et al, 2013).…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation